1975
DOI: 10.1111/j.1748-1716.1975.tb05887.x
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Potential and Conductance during Piocytosis Induced in Amoeba proteus with Alkali Metal lons

Abstract: An investigation of the relationship between the polarized state of the membrane and the onset and the intensity of pinocytosis was made in Amoeba proteus. Membrane potential and input resistance was in all instances found to decrease in approximate proportion to the number of channels when pinocytosis was induced by a variety of alkali metal ions at varying pH. Channels began to appear when the membrane was depolarized to -30 mV by the inducer of pinocytosis. With all inducers the maximum pinocytosis was enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

1979
1979
1996
1996

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…This rise in free calcium would then initiate solation-contraction coupling, forming fibrils derived from the cortex (72), which would then generate the forces required for channel formation. This proposed mechanism correlates well with many of the original suggestions by Brandt (14), Nachmias (46), Jeon and Bell (34), Josefsson et al (37), and recently by Klein and Stockem (38) (Fig . 11).…”
Section: Correlation Between Aequorin Luminescence and Pseudopod Formsupporting
confidence: 74%
See 2 more Smart Citations
“…This rise in free calcium would then initiate solation-contraction coupling, forming fibrils derived from the cortex (72), which would then generate the forces required for channel formation. This proposed mechanism correlates well with many of the original suggestions by Brandt (14), Nachmias (46), Jeon and Bell (34), Josefsson et al (37), and recently by Klein and Stockem (38) (Fig . 11).…”
Section: Correlation Between Aequorin Luminescence and Pseudopod Formsupporting
confidence: 74%
“…Brandt and Freeman (15) and Gingell and Palmer (27) demonstrated that the initiation of pinocytosis is accompanied by a decrease in electrical resistance of the plasmalemma, implying an increase in the ionic permeability . This might be related to the observation that the binding of pinocytosis inducers causes membrane depolarization (7,36,37) regulated by extracellular calcium and pH (32,37,51,52). Gingell (28) has suggested that the negative surface potential might be decreased when the inducers were bound and that this would directly affect the local membrane potential.…”
Section: Correlation Between Aequorin Luminescence and Pseudopod Formmentioning
confidence: 99%
See 1 more Smart Citation
“…Where Marshall's mc~lium (pH 4.0) is used, the composition is as follows: 0.26 mM KH~P0~, 0.05 mM MgSO(, 0.5 mM CaCI~, 0.14 mM KCI, pH 4.0 (sfight pH adjustments with 0.1 M HCl are performed at 4°C). Addition of KC1 brings the [K +] to that of normal Marshall's, deemed necessary because membrane potential, streaming velocity and pinocytic activity of amebae are affected by [K +] (4,5,20). Tetrahymena pyriformis, also obtained from Carolina Binloglcal Supply, are grown axenically in nutrient medium (1.5% Proteose peptone, 0.1% yeast extract, 0.2% dextrose).…”
Section: Methodsmentioning
confidence: 99%
“…However, the culture conditions for the organisms in these investigations were different from those used in the present study and it is possible that discrepancies arise from differences in the characteristics of the recording system and electrodes used. A difference in the value for membrane potential probably resulting from a difference in the technique for impaling cells has been demonstrated in Amoeba proteus (Joseffson, 1966;Joseffson, Holmer & Hansson, 1975).…”
Section: Discussionmentioning
confidence: 99%